Metode Pendidikan Orang Tua Kepada Anak (Studi Pada Orang Tua Anak Di Gang Ori Ii Papringan Sleman Yogyakarta) - Imam Hanafi; Eko Adi Sumitro (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
This study tries to examine the educational methods applied by parents to children in one alley in the Yogyakarta Region, with Gang Ori II Papringan Sleman Yogyakarta as a location. Using a qualitative naturalistic approach with descriptive analysis methods. Data collection is done by participant observation, in-depth interviews, and documentation. The data obtained were analyzed using Non-Statistical Spradley analysis. The results of this study indicate that based on the above explanation it can be concluded that, parents who live in Gang Ori II Papringan Sleman Yogyakarta vary in terms of the method of educating their children. There are those who educate their children with exemplary methods, there are also those who use the method of advice or customs. And some also use the method of punishment or sanctions.